Different surgical approaches for the treatment of adjacent segment diseases after anterior cervical fusion: A retrospective study of 49 patients. Issue 23 (June 2017) - Wang, Feng; Wang, Peng; Miao, De-Chao; Du, Wei; Shen, Yong
Abstract : Abstract: Studies in the literature have not delineated the surgical approaches of symptomatic adjacent segment diseases (ASDs) in patients undergoing reoperation after an initial anterior cervical fusion (ACF). The purpose of this study was to determine the optimal surgical approaches of ASD and the incidence of the dysphagia after reoperation. This was a retrospective study of 49 patients with ASD after an initial ACF surgery, which had undergone a reoperation at our medical center between January 2010 and December 2014. The surgical approaches were used by anterior cervical discectomy and fusion (ACDF), ACDF with the Zero-profile device, laminoplasty, and laminectomy with internal fixation. Patients were classified according to the different surgical approaches of anterior (n = 38) versus posterior (n = 11) groups and ACDF (n = 25) versus Zero-P (n = 13) groups. Clinical evaluations were performed preoperatively and repeated in 24 months after operation. This retrospective study included 26 men and 23 women with a mean age at revision surgery of 54.3 years and ASD onset time of 7.3 years. The patients were followed up with an average of 4.1 years. The reoperation rate was 5.4% in this study. The Japanese Orthopaedic Association (JOA), Neck Disability Index (NDI), and visual analogue scale (VAS) scores demonstrated significant improvements compared with preoperative in both anterior and posterior groups ( P  < .05). However, there were no differences between the 2 groups ( P  > .05). The operation time of ACDF group was more than Zero-P group, with significant differences ( P  < .05). However, there were no differences in JOA, NDI, and VAS scores between the ACDF and Zero-P groups pre- and postoperative ( P  > .05). A total of 12 (24.5%) patients had dysphagia after reoperation. The incidence of dysphagia in Zero-P group (1/13) was less than ACDF group (11/25), with significant differences ( P  < .05). There were no cases of major neurological or vascular complications, and wound complications. The clinical situation, initial operation, and secondary preoperative imaging findings were analyzed comprehensively, anterior or posterior approach were chosen, which can effectively relieve spinal cord compression and improve spinal cord function. In ACDF with the Zero-profile device surgery, there was no need to remove the previous internal fixation, shorten the operation time, and reduce the incidence of postoperative dysphagia.